Influência do 5-fluorouracil nos tecidos periodontais normais e sobre a evolução da doença periodontal experimental induzida - Novaes, Vivian Cristina Noronha [UNESP] (2013)
The present study evaluated by histomorphometric, immunohistochemistry and Alkaline Phosphatase (ALP) analysis the effects of the chemotherapeutic 5-fluorouracil (5-FU), in the normal periodontal tissues, in the evolution of experimental periodontitis (EP) and in the mechanical periodontal treatment Scaling and Root Planing (SRP). 150 rats were treated, of which 92 were used and randomly divided into 6 groups of the following treatments: Group C (n = 24) - animals not treated with 5-FU without PE, contralateral area of groups EP and EP + SRP that were used as negative control. EP group (n = 16) - animals with EP. Group EP + SRP (n = 18) - animals with EP and treated locally by SRP. Group 5-FU (n = 24) - animals treated systemically with 5-FU. Group 5-FU + EP (n = 16) - animals treated systemically with 5-FU and with EP induction. Group 5-FU + EP + SRP (n = 18) - animals treated systemically with 5-FU, with EP and treated locally with SRP. The EP was induced by placing a cotton thread around the left mandibular first molar. In the animals of the groups 5-FU, 5-FU + EP and 5-FU + EP + SRP, 5-FU was administered at the time of induction of EP, and after 48 hours. After 7 days of evolution of EP, the animals of groups EP, EP + SRP, 5-FU + EP and 5-FU + EP + SRP, the ligature was removed and the groups PE + SRP and 5-FU + EP + SRP were treated locally with SRP. The animals were sacrificed at 7, 15 and 30 days after removal of the bandage. Were obtained from serial sections of 4 mm thick in the mesio-distal and stained with Hematoxylin and Eosin or Masson's Trichrome. The Percentage of Bone in the Furcation (PBF) was evaluated by histomorphometric analysis...